Tanggung Jawab Anak dalam Memelihara Orang Tua Terkait Ketentuan Pasal 46 Ayat (2) Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Fathanah, Rahdinal; Sulistyarini, Rachmi (Universitas Negeri Malang, 2020)
The purpose of this writing is to analyze the form of responsi-bility of children in caring for parents related to the provisions of Article 46 paragraph (2) of Law number 1 of 1974 concerning Marriage accord-ing to the perspective of Civil Law, Customary Law especially Balinese Customs and Islamic Law and analyze the form of legal protection for parents who does not get care by children. The method used is the legal approach and conceptual approach. The results of this study are a form of children's responsibility in looking after parents, according to the per-spective of civil law, to be material. Meanwhile, according to the per-spective of customary law, especially Balinese custom and Islamic legal perspective, it is material and immaterial. The form of preventive legal protection for parents who do not receive care by children in the form of a District Court stipulation regarding the inability of children to provide for their parents, and the form of repressive legal protection for parents who do not get care by children in the form of civil lawsuits reg